PENGARUH STRATEGI TV COMMERCIAL TERHADAP HASIL BELAJAR AFEKTIF MATA PELAJARAN PAI DAN BUDI PEKERTI SISWA KELAS 8 DI SMP NEGERI 5 YOGYAKARTA - Izmi Rafi Hamdini; Eva Latipah (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
TV Commercial Strategy is a learning strategy by forming a team in random based on the number of the students in a classroom that are assigned to create a TV Commercial or other forms of advertisements that is relevant to the learning materials. TV Commercial Strategy aims to develop cooperation among students. This research belongs to experimental research using PreTest-PostTest Design Experiment. The data were collected through self-assessment, interviews, and documentation methods. The results of t-test show that TV Commercial Strategy influences the affective learning results in the subject of PAI and Character, It can be seen from the score of t table at the significant rate of 5%, which is as much as 2,04. The score of T is (0,007) < 0,05. Because t-value is > t table (-2,887 > 2,04), there is significant difference. The influence of TV Commercial Strategy on the affective learning result can be seen from the score of R 2 , which is as much as 0,687 = 0,47 (47%). The rest of the percentage, which is as much as 53% is from other factors influencing the improvement of learning results.